Harmful results of improper fitted wheelchair – case study - Mikołajewska, Emilia (Journal of Medical Science, 2017)
Wheelchair is perceived basic orthopaedic equipment, both for permanent and temporary use. Proper wheelchair fitting, and correct education of both medical staff, patients, and their families/caregivers may influence increased awareness of threats, limitations, and results of incorrect patient’s positioning in wheelchair. Basic knowledge and experience may significantly reduce consequences in aformentioned area, and influence to shorter and more effective therapeutic process. Aim of this paper is to discuss possible problems resulting from improper wheelchair fitting on the basis of presented case study, explore the relationship between improper wheelchair fitting and limitations of wheelchair users independence, mobility, and life quality based on own experience and propose solutiopna and direstions of further research.